Percepciones de la música popular del Ecuador a partir de la fusión de ritmos y los cambios de identidad de quienes lo escuchan en el cantón Latacunga - Maisincho Jiménez, Cristian Patricio (2017)
This research has the theme "Perceptions of the popular music of Ecuador from the fusion of rhythms and the changes of identity of those who listen to it in the canton Latacunga", which raised as a research problem the changes they have experienced In the identity of those who listen to popular music, from the fusion of rhythms, in this study, the objective was to identify the changes in the identity of those who listen to popular music, from the fusion of rhythms, in which once detected The problem proceeds to the construction of the Theoretical Framework to properly base the research topics that in this case in particular are the changes that have experienced in the identity of those who listen to popular music, from the fusion of rhythms, Is true by means of the fusion of rhythms that is the union of different rhythms, the old songs with Ecuadorian own rhythms has returned to revive, is also undermining the originality of the same, which in one way or another damages the cultural identity of those who listen to it, this information is based on books, magazines, and the Internet; The methodology of the research was based on a descriptive, exploratory, qualitative-quantitative perspective and, with the application of a field research design where instruments were applied for the processing of the information collected from the survey and interview applied to the students of The career of Social Culture and musicologist of the Technical University of Cotopaxi, respectively, regarding the changes that have occurred in the identity of those who listen to popular music, starting from the fusion of rhythms, proceeding to analyze statistically the data obtained, which allowed to establish the This study constitutes an important part of contributing to the preservation of the cultural identity that currently threatens to disappear.